Public tenders and organised crime (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
Over the last decades the activities related to the public works contracts and supply contracts, being one of the most strategical and considerable aspects for the economy of the country, have been also one of the main areas of the public administration influenced by organized crime groups.  The aims of this essay are trying to explore the reasons and the advantages which let organized crime to interfere with the legal economy and in particular the public works and supply contracts activities. It will analyses the evolution of the interference techniques during the last years with a particular emphasis on the main steps of assignment for these types of contracts. In addition, it will examine the evolution of legislation in this subject area as well pointing out the levels of criticality. Lastly it will introduce the Italian’s National Anti-Corruption Authority, institutional body which carries out a wide range of important activities in preventing corruption, promoting transparence and providing supervision in these types of activities related to public works contracts.Keywords: Public procurement; public works contracts and supply contracts; organized Crimes; National Anti-Corruption Authority; Public Administration